The Process of Internalizing the Values of Tazkiyatun Nufus through the Bidayatul Hidayah Book: A Case Study at the Raudatul Ulum Islamic Boarding School Jember - Hasi, Muhamad Umar (Universitas Nurul Jadid, 2026)
This study aims to analyze the process of internalization, implementation, and habituation of the values of Tazkiyatun Nufus (purification of the soul) in the book Bidayatul Hidayah by Imam al-Ghazali at the Raudlatul Ulum Islamic Boarding School, Sumber Wringin Sukowono Jember. This study uses a qualitative approach with a case study design to deeply understand the practice of spiritual education and character formation of students in the context of Islamic boarding schools. Data were collected through in-depth interviews with kyai and ustaz, participatory observation of students' activities, and documentation of learning activities and Islamic boarding school culture. Data were analyzed thematically through the process of reduction, categorization, and drawing conclusions. The results of the study indicate that the internalization of the values of Tazkiyatun Nufus is carried out through learning classical books, spiritual guidance, and the exemplary behavior of kyai and ustaz. Its implementation is reflected in the daily practices of students such as congregational prayer, dhikr, muhasabah, and training in patience and self-control. The habituation process is formed through the pesantren culture, which emphasizes steadfastness in worship, simplicity of life, discipline, and collective responsibility. Theoretically, this research contributes to the development of an Islamic character education model based on Tazkiyatun Nufus ( the practice of self-discipline) within the pesantren tradition. Pedagogically, these findings demonstrate that integrating classical textual teaching, spiritual practices, and religious habituation can be an effective strategy for strengthening character education in pesantren and other Islamic educational institutions.